Integrated water management for municipalities in South Africa - DU PLESSIS, J. A (Proceedings of the Institution of Civil Engineers. Municipal engineer, 2014)
South Africa is facing serious water shortages within the next 25 years and effective water demand management forms an integrated part of the possible solution. Municipalities are responsible for the majority of the water supply functions in South Africa, but they are challenged by limited funding opportunities and a lack of capacity. Water demand management projects in municipalities focus mainly on solving the water supply shortfall instead of implementing solutions as part of an integrated water resource strategy. The main objective of the research was to develop a model to guide the municipalities through the decision-making process to manage their water situation in a more sustainable and integrated manner. The model is supported by the development of an implementation and effective public participation process. The model also makes provision for six decision support systems, one for each step of the integrated water cycle (i.e. water resources, water treatment, distribution, consumer demand, waste water treatment and institutional aspects). The role and responsibility of political decision-making is also highlighted. The model is supported by a score card system, which enable a municipality to assess its performance or readiness to implement water demand management in an integrated and sustainable manner.